(untitled) (Academia Journal of Medicine, 2020)
Background : Meningitis is serious and a life-threatening condition among any age group associated with serious mortality and morbidity. The objective of the present research was to assess the efficiency of CSF lactate in differentiating bacterial/ pyogenic from non-pyogenic meningitis. Subjects and Methods: A hospital-based one-year prospective study was conducted at a tertiary care hospital in Gujarat. The study was performed at the department of General medicine for a period of one year. All the cases suspected of meningitis above 18 years of age irrespective of sex were admitted and clinically evaluated. The Diagnosis of meningitis was made on account of various clinical symptoms and signs. Like headache, nausea, presence of kernig’s sign, altered sensorium, cranial nerves palsies, hemiparesis, seizures, etc, Results: The mean total cell count was highest in cases of pyogenic meningitis with a mean of 840.50 and SD of 112.30 than viral and tubercular meningitis. However, no statistical significance was associated with total count and types of meningitis. (P> 0.05) Lactate levels of the CSF were elevated than normal in both pyogenic and tubercular than viral, however, the mean CSF lactate was higher in pyogenic than tubercular. A clear statistical significance was observed in CSF sugar/blood glucose ratio and CSF lactate levels in this study (p≤0.05). Conclusion: CSF lactate level is a rapid, quite inexpensive and unpretentious process, important diagnostic indicator in the premature demarcation of pyogenic meningitis and tubercular meningitis from viral meningitis, serving in the premature organization of proper action and diminishing transience and impediments. Early detection may help in early decision on the type and institution of appropriate management could reduce the mortality and morbidity of meningitis.